RATING AND ECONOMIC ASSESSMENT OF LATE APPLES - Матвієнко, Андрій; Мулярчук, Оксана; Баліцька, Людмила; Свинарчук, Олена; Юшкевич, Марина; Войцехівський, Володимир; Пошкребньов, Віталій (SWorldJournal, 2022)
A number of important indicators of common winter apple varieties have been analyzed. The rating of the studied varieties is calculated. The most valuable varieties according to the studied economic indicators are: Horodyshche, Aurora Crimean, Crimean, Sc